Lipid Involvement in Neurodegenerative Diseases of the Motor System: Insights from Lysosomal Storage Diseases - Dodge, James C. (Frontiers in Molecular Neuroscience, 2017)
Lysosomal storage diseases (LSDs) are a heterogeneous group of rare inherited metabolic diseases that are frequently triggered by the accumulation of lipids inside organelles of the endosomal-autophagic-lysosomal system (EALS). There is now a growing realization that disrupted lysosomal homeostasis (i.e., lysosomal cacostasis) also contributes to more common neurodegenerative disorders such as Parkinson disease. Lipid deposition within the EALS may also participate in the pathogenesis of some additional neurodegenerative diseases of the motor system. Here, I will highlight the lipid abnormalities and clinical manifestations that are common to LSDs and several diseases of the motor system, including amyotrophic lateral sclerosis, atypical forms of spinal muscular atrophy, Charcot–Marie–Tooth disease, hereditary spastic paraplegia, multiple system atrophy, Parkinson disease and spinocerebellar ataxia. Elucidating the underlying basis of intracellular lipid mislocalization as well as its consequences in each of these disorders will likely provide innovative targets for therapeutic research.